The experiences of young people who were raised by social fathers in Gauteng - Matjila, Matsie (My University, 2016)
Historically in Southern Africa social fathers have played a significant role in the lives of children particularly in African families. Also for many decades, the stability of family relationships and the role of biological fathers have significantly eroded due to historical factors such as migrant labour system and the high prevalence of absent father. The purpose of this study is to explore the experiences of young people raised by social fathers instead of biological fathers. The study will use a qualitative research approach in conjunction with exploratory design. Data gathering will be conducted through ten semi-structured individual interviews and be analysed through thematic analysis. The study will add value on understanding the importance of social fathers; connection and support to determine the contribution that social fathers make to their children. The study revealed that young men and women have good relationship with their social fathers although there are boundaries in communication with their social fathers. These social fathers have played provider and teacher roles in their lives. They have more of a father and son/daughter relationship; hence they have a good relationship. Some come from a low family environment and have challenges while others see their family environment as good. Most young men and women are raised by their grandfathers, while others are raised by uncles, brothers and stepfather as their social fathers. They do not have any form of relationship with their biological fathers and this is because their biological fathers passed on while for others it is because they do not know their biological fathers. KEY WORDS: Men, women, fatherhood, social father, family.
In partial fulfilment of the requirements for the degree of Bachelor of Social Work